Draining the tobacco swamps: Shaping the built environment to reduce tobacco retailer proximity to residents in 30 big US cities. (May 2022) - Combs, Todd B.; Ornstein, Joseph T.; Chaitan, Veronica L.; Golden, Shelley D.; Henriksen, Lisa; Luke, Douglas A.
Abstract: Combining geospatial data on residential and tobacco retailer density in 30 big US cities, we find that a large majority of urban residents live in tobacco swamps – neighborhoods where there is a glut of tobacco retailers. In this study, we simulate the effects of tobacco retail reduction policies and compare probable changes in resident-to-retailer proximity and retailer density for each city. While measures of proximity and density at baseline are highly correlated, the results differ both between effects on proximity and density and across the 30 cities. Context, particularly baseline proximity of residents to retailers, is important to consider when designing policies to reduce retailer concentration. Highlights: Tobacco retailer density and resident-to-retailer proximity are highly correlated. The impacts on density and proximity differ for retailer reduction policies. The impact of such policies is highly dependent on the existing retail environment. Tailoring of policies and policymaker knowledge of the environment are central.